Testing Baumol: Institutional quality and the productivity of entrepreneurship - Sobel, Russell S. (Journal of Business Venturing, 2008)
Baumol's [Baumol, W.J., 1990. Entrepreneurship: productive, unproductive and destructive. Journal of Political Economy 98 (5), 893–921] theory of productive and unproductive entrepreneurship is a significant recent contribution to the economics of entrepreneurship literature. He hypothesizes that entrepreneurial individuals channel their effort in different directions depending on the quality of prevailing economic, political, and legal institutions. This institutional structure determines the relative reward to investing entrepreneurial energies into productive market activities versus unproductive political and legal activities (e.g., lobbying and lawsuits). Good institutions channel effort into productive entrepreneurship, sustaining higher rates of economic growth. I test and confirm Baumol's theory, and discuss its significance to the literature, economic prosperity, and policy reform.